A Rare Presentation of Invasive Nontypeable Haemophilus influenzae With Systemic Involvement: A Case Report - Hajra Nosheen; Lochan Bellamkonda; John George Youssef; Abhijeet Ghatol; Shagufta Naz Ali (Case Reports in Infectious Diseases)
Haemophilus influenzae (H. influenzae) is a common organism that causes noninvasive infections in the respiratory tract. Lately, there has been an increasing incidence of invasive diseases with nontypeable strains not covered by Hib vaccines. We discuss a case of a middle-aged male with sickle cell trait and gout who presented with altered mentation and polyarthralgia. On investigations, he had H. influenzae bacteremia on two sets of blood cultures with dissemination to meninges and joints, causing acute encephalopathy and polyarthralgia. The initial results of arthrocentesis and lumbar puncture were sterile. However, PCR analysis of the fluid revealed nontypeable H. influenzae. The patient required mechanical ventilation and vasopressor support given sepsis but recovered after extended antibiotics and multiple surgical debridements. Our case highlights the importance of maintaining a high suspicion of invasive disease in decompensated patients and the role of advanced diagnostics in treatment and outcome.